Van Linck and Janet Hethorn - Unidentified photographer (Colorado State University. Libraries, 1988)
Photograph of Friends of the Gustafson Gallery president, Van Linck, and Curator, Janet Hethorn, posing at the June 1988 farewell party for Hethorn.
Keywords: Fashion -- History; Fashion -- Exhibitions